Case Report: Discontinuous Spontaneous Ventilating Anesthesia for McKeown Esophagectomy by Laryngeal Mask: A Case Series—A Novel Approach of Discontinuous Spontaneous Ventilating Anesthesia for Esophagectomy - Xu, Qiaoqiao; Mo, Xuan; Xiong, Juan; Zhang, Yi (Frontiers in Surgery, 2021)
Double lumen endobronchial ventilation in McKeown esophagectomy is common for esophageal cancer. In spite of most patients could be extubated immediately after surgery under adequate multimodal analgesia, still some patients require extended mechanical ventilation or airway support post-surgery because of pain or difficult respiration. The present study reported a novel challenge for McKeown esophagectomy with discontinuous spontaneous ventilating anesthesia by the laryngeal mask. Three esophageal cancer patients underwent McKeown esophagectomy under discontinuous spontaneous ventilating anesthesia with local and regional analgesia and appropriate sedation. Two of them were accomplished under non-intubated video-assisted thoracoscopic surgery (NIVATS), and then, the abdominal and neck surgery was managed under laryngeal mask airway with appropriate muscle relaxation. One patient was endured high PetCO2 level, and converted to regular double lumen endobronchial intubation for safety. However, from the two successful cases, we still proved that the discontinuous spontaneous ventilating anesthesia achieved the same anesthetic effect as bronchial intubation under general anesthesia for McKeown esophagectomy, which reduced the postoperative pharyngeal discomfort, might be beneficial to the patients for enhanced recovery after surgery (ERAS).